MSc Entrepreneurship Business Plan PATIENTS TOGETHER - Goelles, Rebecca (2016)
Business plan for PATIENTS TOGETHER, a social health network for people affected by chronic health conditions. Developed and written by Rebecca Goelles as part of the MSc Entrepreneurship, Innovation and Management.